2008
DOI: 10.1016/j.jvs.2008.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Growth predictors and prognosis of small abdominal aortic aneurysms

Abstract: Lipid-lowering drug treatment and initial AAA diameter appear to be independently associated with lower AAA growth rates. The risk of rupture of these small abdominal aortic aneurysms was low, which pleads for watchful waiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 34 publications
7
110
3
2
Order By: Relevance
“…The publication dates of the 15 potentially eligible studies 13,22,[29][30][31][32][33][34][35][36][37][38][39][40][41] ranged from 1994 to 2009, with patient recruitment from 1976 to 2005. Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication dates of the 15 potentially eligible studies 13,22,[29][30][31][32][33][34][35][36][37][38][39][40][41] ranged from 1994 to 2009, with patient recruitment from 1976 to 2005. Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 10 were prospective studies 13,22,[34][35][36][37][38][39][40][41] (including three randomised trials), four included both retrospective and prospective data 29,30,32,33 and one study reported only retrospective data. 31 Aneurysm growth was the primary outcome measure in 10 of the 15 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of them, we identifi ed seven eligible studies [9][10][11][12][13][14][15] reporting the association of BMI and AAA growth rates, which included data on a total of 3,768 AAA patients. The patient and AAA characteristics, the details of diameter measurement, and the association between BMI and AAA growth rates are summarized in Table 1 In a prospective study by Burillo et al [13], 122 male patients with a >30 mm AAA were scanned annually with a mean observation time of 8.1 years.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in an observational cohort study by Schlösser et al [10] from the SMART [Second Manifestations of ARTerial disease] study, 147 patients (65±7.7 years) with a 39±6.8 mm AAA were selected for a study on expansion rates in 4.0±2.5 years of follow-up time. A univariate analysis revealed that BMI was not associated with diff erences in expansion rates (unadjusted estimated diff erence in annual growth per 1-kg/m 2 increase in BMI, -0.06 mm/year; 95% CI, -0.20 to 0.09 mm/year; P = 0.432).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation